Fabrication, thermal and electrical properties of polyphenylene sulphide/copper composites - Goyal, R. K.; Kambale, K. R.; Nene, S. S.; Selukar, B. S.; Arbuj, Sudhir S.; Mulik, Uttam P. (Materials Chemistry and Physics, 2011)
The thermal and electrical properties of high performance poly(phenylene sulphide) (PPS) composites reinforced up to 31 vol% Cu particles were investigated to be used as materials for electronic applications. The thermal stability and char yield of the composites increased significantly. Both pre- and post- glass transition coefficient of thermal expansion (CTE) of composites decreased significantly. The microhardness was increased by more than 50% compared to pure PPS matrix. Microhardness and CTE of composites correlated well with the rule of mixtures. A percolation threshold about 6 vol% Cu was obtained. The electrical conductivity was increased by about eight orders of magnitude for 18 vol% composite. Dielectric constant and dissipation factor of composites at 1 MHz was increased by about 6-fold and 70-fold compared to matrix, respectively. They decreased gradually with increasing frequency up to 1 MHz and thereafter, there was insignificant change. The scanning electron microscope showed almost uniform distribution of Cu particles in the matrix. Owing to better dimensional stability and good electrical properties, these composites are very promising for electronic applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric property; Electrical conductivity; hardness; Thermal expansion

PEEK/SiO2 composites with high thermal stability for electronic applications - Goyal, R. K.; Rokade, K. A.; Kapadia, A. S.; Selukar, B. S.; Garnaik, Baijayantimala (Electronic Materials Letters, 2013)
Thermal and mechanical properties of new high performance polymer matrix composites based on poly(etheretherketone) (PEEK) as matrix and crystalline-silica (SiO2) as reinforcement were discussed for application in electronic packaging substrates or printed circuit boards. The content of SiO2 was varied between 0 and 50 wt. %. Scanning electron microscopy showed uniform dispersion of SiO2 particles in the matrix. Thermogravimetry analysis showed significant increase in thermal stability and char yield with increase in SiO2 content in the matrix. Differential scanning calorimetry showed that SiO2 had a heterogeneous nucleating effect on PEEK, leading to an increase in peak temperature of crystallization and onset crystallization temperature of the composites compared to a pure matrix. The microhardness increased approximately 42%. A modified rule of mixtures with a strengthening efficiency factor equal to 0.06 fit the data nicely. The results show that the prepared PEEK/SiO2 composites may have potential applications in electronics.
Keywords: hardness; PEEK; polymer matrix composites; Thermal properties